The Effectiveness of Mindfulness Training on Achievement Motivation and Academic procrastination of Students - mohadeseh sayyadi ghasabeh (Islamic Azad University, Tabriz Branch, 2021)
The aim of this study was to investigate the effectiveness of mindfulness training on students' achievement motivation and academic procrastination. The research method was quasi-experimental with pre-test and post-test design with control group. The statistical population of this study included 106 sixth grade male students in Rasht City in the academic year 2019- 2020 Who were selected by available sampling and 30 of these students who received the lowest score in Achievement Motivation Questionnaire and the highest score in Academic Procrastination Questionnaire They were selected as a research sample and randomly assigned to two groups of control (n = 15) and experimental (n = 15). The experimental group received mindfulness training in 8 sessions of 90 minutes but the control group did not receive any intervention. For data collection, Hermans Progress Motivation Questionnaire and Solomon and Roth Bloom Academic Procrastination Questionnaire were used. The collected data were analyzed using multivariate analysis of covariance. The results showed that after mindfulness training, the average of the experimental group in the variables of achievement motivation and components of academic procrastination (preparing for the exam and preparing for homework) there is a significant difference (P< 0/01). In conclusin, it can be said that the use of mindfulness training is effective in improving the motivation for progress and reducing students' academic procrastination.